Synergetic effect of Egyptian propolis in immunization of BALB/c mice against bovine cysticercosis - Omnia Mohamed Kandil; Somia Ayesh Nassar; Soad Mohamed Nasr; Hatem Abdel Mawgoud Shalaby; Seham Hendawy; Faragalla Mohamed El Moghazy (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To evaluate the synergetic effect of an ethanolic extract of Egyptian propolis in immunization of BALB/c mice with Taenia saginata (T. saginata) crude antigen against bovine cysticercosis, with reference to its effects on liver and kidney functions. Methods: Sixty female mice BALB/c strain weighing 20 to 25 g and 6-8 weeks old were randomly allocated into six groups of ten mice each. Mice in groups 1 and 2 (G1 and G2) were immunized intraperitoneally with 100 µg of T. saginata crude antigen in 100 µL phosphate buffer saline emulsified in Freund's adjuvant. Besides, the mice in G2 were administered with propolis extract simultaneously with immunization. Control mice were either administered with propolis extract (G3) or injected with the same volume of phosphate buffer saline emulsified in Freund's adjuvant (G4). The mice in G5 were non-immunized infected control while, those in G6 were non-immunized non-infected control. Two weeks after the last immunization, each mouse was challenged intraperitoneally with 5 000 oncospheres except those of G6. Ethanolic extract of propolis was prepared at a dose 50 mg/kg body weight. Results: After 24 weeks of challenge, the mice in G2 showed the highest level of protection (100%), with no cyst being detected rather than mice in G1 (33.3% protection). Additionally, the ELISA results, in this study, showed higher antibody titer in G2 with reduction the alteration in liver and kidney functions compared to G1. Conclusions: Egyptian propolis could increase the level of protection against experimental challenge infection with T. saginata eggs when administered simultaneously with immunization. Furthermore, it could enhance the production of antibodies to immunized antigen and decrease the alteration in liver and kidney functions.